Rheumatic Heart Disease Causes Heart Failure. How is It Treated? - Dian Rozani (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlight: Rheumatic heart disease is among a leading cause of heart failure in school-age children. It discusses how to proper manage rheumatic heart damage Abstract: Rheumatic heart disease is the leading cause of heart failure in school-age children, affects 30 million people worldwide, and is still prevalent, especially in developing countries. Rheumatic heart disease was the result of untreated acute rheumatic fever. Knowledge of the proper management should be encouraged in those with rheumatic fever to halt the progression of cardiac damage that can lead to heart failure. This article discusses one such case. Case Summary. A 13-year-old girl complained of breathlessness during the activity, which improved with rest. She had a history of multiple joint pain and recurrent upper respiratory infection, which was not treated with antibiotics. On physical examination, the blood pressure was 90/60 mmHg, heart rate 128 bpm, facial and palpebral swelling, and the jugular vein pressure increased 5+3 cm H2O. The heart sound was S1>S2, regular with gallop and murmur in mitral, aortic, pulmonary, and tricuspid valves. Hepatomegaly and swelling of both lower extremities were discovered. Laboratories tests found ASTO 400 IU/ml. Chest X-Ray showed cardiomegaly. Echocardiography showed the regurgitation of mitral, aortic, tricuspid, and pulmonary valves. Discussion. The patient was diagnosed with heart failure fc. NYHA II ec rheumatic heart disease and treated with penicillin benzathine 1.2 units, furosemide injection 30 mg b.i.d, spironolactone 25 mg b.i.d, tenace 5 mg q.d, and prednisone 5-4-4 mg t.i.d. Adequate management of acute rheumatic fever can reduce the recurrence, prevent rheumatic heart disease and cardiac deterioration, and improve quality of life.